Clinicopathological correlation of ocular pigmented lesions - Basnet, Alka; Shakya, Rashmi (Journal of Pathology of Nepal, 2025)
Background: Ocular pigmented lesions, ranging from benign nevi to malignant melanomas, present a diagnostic challenge due to their varied clinical appearance. This study aimed to establish a definitive diagnosis correlating epidemiological, clinical, and histomorphological features of these lesions. Materials and Methods: A hospital-based cross-sectional study was conducted from September 2021 to February 2023, over 18 months at Universal College of Medical Sciences and Teaching Hospital. After ethical clearance (Reference number: UCMS/IRC/108/21), 42 cases of ocular pigmented lesions received in the Department of Pathology were evaluated histologically using Hematoxylin and Eosin-stained sections. Statistical analysis of the data was performed using Statistical Package of the Social Sciences version 25. Results: Of 42 patients (25 females, 17 males; mean age 26.36 ± 18.15 years), the vast majority, 40 (95.2%), were diagnosed as benign nevi, with only two cases (4.8%) of malignant melanoma. The most common lesion was compound nevus 20 (47.6%), followed by subepithelial nevus 14 (33.3%). Bulbar conjunctiva 19 (45.2%) and eyelid 18 (42.8%) were the predominant sites. Most lesions presented as a nodular 24 (57.1%), light-brown 22 (52.4%) mass or spot. Clinical diagnosis of nevus showed 100% concordance with histopathology, whereas clinical suspicion of melanoma had a low concordance (33.3%), with many such cases turning out to be nevi on histology. Conclusions: Histopathological examination remains the gold standard for accurate diagnosis of ocular pigmented lesions. While benign nevi are far more common and typically affect a younger demographic, clinical features alone can be misleading, especially in suspected melanoma cases. High index of suspicion and routine biopsy are imperative for correct diagnosis and management